(untitled) (Ágora de Heterodoxias, 2026)
This article presents the Model of Anchors and Situated Decisions in the Community (MADESC an analytical-heuristic framework, built through meta-synthesis and thirty years of participant observation, that integrates three dimensions (real, planned, emergent) and three anchors (identity, relationship, norms). The core idea is that situated decisions emerge from normative hybridization: a creative fusion between project rules and the community’s formal and informal norms. MADESC proposes two conceptual shifts: the emergent as a source of solutions rather than a deviation, and non-linearity as the key to viability. It includes a typology of decision configurations (synergy, creative tension, dissonance).